Management model of the quinteto in the labor performance of the workers of the Educational Management Unit – Huánuco - Veramendi-Mazza, Hebert A. (2019)
The objective of the present investigation was to determine the influence of the Quintet Management Model on the work performance of the workers of the Local Educational Management Unit of Huánuco. The type of research was evaluative. The design of the research was non-experimental. The population of the present research work consisted of 55 workers from the different bodies of the Local Educational Management Unit of Huánuco. 2015. The sample of the present research work was characterized as being non-probabilistic, because it was chosen as director and workers of the Institutional Management Area of ​​the Local Educational Management Unit of Huánuco, for which the sample consisted of 24 workers who work in the Institutional Management Area and in the Pedagogical Management Area of ​​the Local Educational Management Unit of Huánuco. The results arrived at in the present investigation show that the Management Model of the Quintet significantly influences the work performance of the workers of the Local Educational Management Unit of Huánuco, with a level of significance of C = 5% = 0.05, then α = 0 , 05; then 1 - 0.05 = 0.95 = 1 - α, which allows us to state that the hypothesis was tested with 95% reliability and an error of 5%. The conclusion reached was: The application of the theoretical and practical foundations of the Management Model of the Quintet, contribute effectively in the management of the work performance of the workers of the Local Educational Management Unit of Huánuco.